PENGOLAHAN DATA PADA PUSKESMAS MARGOREJO PATI MENGGUNAKAN WEB (Information Technology and Telematics, 2014)
Abstrak - Processing data that is in the health center Pati Margorejo still use manual. Patient data, drug data collection, data collection physicians still manually. The reports are sent to the District Health Office Pati already using the computer but not computerized and not automatically use the web. The purpose of this research is to design and build information systems processing data at the health center web-based Margorejo Starch. This information system design methods and prototypes for using PHP programming language and the MySQL database to its design using UML (Unifed Modeling Language). System-generated web home menu contains PHC profile Margorejo Starch, master menu has submenus input patient data, physician data input and data input drug, on the menu there is a submenu transactions and history of the patient's medical record, whereas on the menu there is a submenu report drug reports and reports of disease . The resulting system has not been implemented in PHC Margorejo Starch and reports generated not in accordance with Health Department standards Pati thus necessary to develop the system further. Keywords: Information Systems, Data Processing, PHP MySQL, WEB.